Angiotensin-(1-7) oral formulation improves physical performance in mountain bike athletes: a double-blinded crossover study - de Moura, S. S.; Mendes, A. T. P.; de Assis Dias Martins-Júnior, F.; Totou, N. L.; Barbosa Coelho, D.; de Oliveira, E. C.; Motta-Santos, D.; Souza dos Santos, R. A.; Kappes Becker, L. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background The ECA2/Ang-(1-7)/Mas axis is shown to be involved in effects mediated by physical exercise, as it can induce the release of nitric oxide (ON) and bradykinin (BK), which are potent vasodilators. The vasodilating action the NO/BK can contribute to increased metabolic efficiency in muscle tissue and central nervous system. The formulation HPß-CD-Ang-(1-7) through its mechanisms of action can be a promising supplement to aid in the maintenance and improvement of performance and may also favor recovery during competitions. The premise of this study was to investigate the effects of acute oral supplementation HPß-CD-Ang-(1-7) on the performance of mountain bike (MTB) practitioners.